Harry White and Barra Boydell (eds), The Encyclopaedia of Music in Ireland (2013) - Solie, Ruth A. (Journal of the Society for Musicology in Ireland, 2015)
A review of Harry White and Barra Boydell (eds), The Encyclopaedia of Music in Ireland, 2 vols (Dublin: University College Dublin Press, 2013), ISBN 978-1-906359-78-2.